Penyuluhan Penguatan Profil Pelajar Pancasila di SMA Negeri 2 Majene - Rahman, Abdul; Najamuddin, Najamuddin; Ahmadin, Ahmadin; Tamrin, Sopian (Edumedia Solution, 2023)
Education is not only related to academic knowledge, but also involves building the character of students. Character education aims to form good attitudes, values and behavior in students. The Pancasila student profile can be a comprehensive framework to guide students in developing good character. On this basis, service activities to disseminate and strengthen the profile of Pancasila students in the school environment need to be carried out, especially at SMA Negeri 1 Majene. Counseling is carried out by building dialogue between the service team and the school including teachers, students and education staff. The results of the service show that the Pancasila Student profile program is well understood by the participants. They try to combine Pancasila values with religious values and local wisdom.